An Analysis Types and Function of Swear Words Used in PewDiePie's Video - Ni Wayan Suastini; I Made Iwan Indrawan Jendra; Afrilya, Tini (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2021)
Language is very important for every people, by using language people can communicate with each other in daily life. There are a lot of studies that discuss language and one of them is swear words. Swear words is a word or phrase that's generally considered blasphemous, vulgar, or otherwise offensive. These are also called bad words, obscenities, expletives, dirty words, profanities. The act of using a swear word is known as swearing. It can be divided into six types; Excretion, Death, Body Function Term, Religious Matter, Mother in Law and Sex Term. The article entitled